Rapid degradation magnesium alloy for petroleum drilling and preparation method of rapid degradation magnesium alloy
By using magnesium alloys with moderate Al and Cu content in oil drilling, the MgAlCu phase and β-Mg17Al12 phase are formed, the rapid degradation of magnesium alloy is achieved, and the problem of incomplete degradation of temporary blocked workpiece materials in the prior art is solved, and the construction efficiency and environmental protection effect are improved.
Patent Information
- Application Number
- CN202411973305.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
There are shortcomings in the sealing effect of temporary blocking workpiece materials in existing petroleum drilling, which are both environmental pollution caused by low degradation rate, and are also prone to degradation but environmental pollution.
A rapid degradation magnesium alloy for petroleum drilling is used, which includes Al: 3.0-5.0%, Cu: 2.0-5.0%, and the balance is Mg and other impurity elements. The alloy contains MgAlCu phase and β-Mg17Al12 phase, and the rapid degradation of the alloy is achieved through galvanic corrosion.
The magnesium alloy has good mechanical properties and degradation properties, and can dissolve itself underground, avoiding the tedious steps of traditional tool recycling and drilling, improving construction efficiency, and reducing reservoir damage and environmental pollution.
Smart Images

Figure CN119776707A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnesium alloy materials, and in particular relates to a fast-degradable magnesium alloy for oil drilling and a preparation method thereof. Background Art
[0002] In recent years, with the continuous growth of global energy demand and the gradual depletion of conventional oil resources, the output of high-quality oil resources has reached its peak and stabilized in most developed oil fields, and its growth potential has become increasingly limited. This situation has forced the energy industry to turn its attention to more complex and difficult-to-extract oil resources, such as low-permeability oil resources and heavy oil, in order to seek new growth points. Therefore, it has become a top priority to develop efficient and innovative oil extraction technologies, especially those that can effectively cope with the challenges of low-permeability formations and heavy oil reservoirs.
[0003] Among many new technologies, the horizontal well staged fracturing process is widely used in the development of unconventional oil and gas resources because it can effectively increase the production and recovery rate of oil and gas wells. This technology achieves effective reservoir transformation by performing staged fracturing along different layers in a horizontal well, but it also brings with it extremely high requirements for interlayer isolation technology. During the underground layered staged fracturing operation, temporary plugging tools must be used to ensure effective isolation between the layers to prevent the fracturing fluid and fluid from flowing into each other and affecting the fracturing effect. However, after the traditional operation method is completed, additional processes are required to recover or drill out these temporary plugging tools, which not only increases the operating cost, but may also cause reservoir damage and environmental pollution.
[0004] However, the mainstream temporary plugging workpiece materials on the market, such as steel and plastic, have obvious shortcomings. Although steel materials have high strength and good durability, their degradation rate is extremely low, and it is difficult to decompose quickly in the natural environment, which can easily cause long-term environmental burdens. Although plastic materials are easy to process and low in cost, they often release harmful substances during the degradation process, causing secondary pollution to the environment. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a fast-degradable magnesium alloy for oil drilling and a preparation method thereof, so as to solve the problem that the temporary plugging workpiece material in oil drilling in the prior art has good plugging effect but is not easy to degrade, or the plugging material is easy to degrade but pollutes the environment.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: A fast-degradable magnesium alloy for oil drilling, characterized by comprising: Al: 3.0-5.0%; Cu: 2.0-5.0%; The balance is Mg and other unavoidable impurity elements; The magnesium alloy contains MgAlCu phase and β-Mg 17 Al 12 Mutually.
[0007] A further improvement of the present invention is: Preferably, the magnesium alloy has a tensile strength of 250-280 MPa and a maximum elongation of 20%.
[0008] A method for preparing the above-mentioned fast-degradable magnesium alloy for oil drilling comprises the following steps: Step 1, weighing the raw materials according to the set mass, placing the raw materials in a heating furnace, and pouring after melting to obtain a semi-continuous casting; Step 2, homogenizing the semi-continuous casting and obtaining a process part after quenching; Step 3, obtaining a magnesium alloy by extruding the process part.
[0009] Preferably, in step 1, the raw materials are pure magnesium ingots, pure aluminum ingots and pure copper ingots.
[0010] Preferably, in step 1, the melting temperature is 750°C and the pouring temperature is 720°C.
[0011] Preferably, in step 1, a mixed protective gas is added during the smelting process, and the protective gas consists of CO2, Ar and SF6.
[0012] Preferably, in step 2, the homogenization temperature is 300-320° C. and the homogenization temperature is 6-8 hours.
[0013] Preferably, in step 2, the quenching temperature is 70°C.
[0014] Preferably, in step 3, the extrusion temperature is 360-380°C.
[0015] Preferably, in step 3, the extrusion ratio is 9:1 and the extrusion speed is 2 mm / s.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a fast-degrading magnesium alloy for oil drilling, wherein the fast-degrading magnesium alloy contains Al and Cu, with the mass percentages being: Al: 3.0-5.0%, Cu: 2.0-5.0%, and the remainder being Mg and other inevitable impurity elements. In the invention, alloying elements are added to Mg to form a second phase, which is mainly a MgAlCu phase and a β-Mg 17 Al 12 Phase affects the degradation performance and mechanical properties of the alloy. Specific analysis shows that the alloy and its composition of the present invention also have the following advantages: (1) MgAlCu phase and β-Mg formed by extruded degraded magnesium alloy 17 Al 12 Phase, due to the large potential difference with the magnesium matrix, is conducive to the formation of micro-batteries, which realizes the degradation of the alloy through galvanic corrosion. At the same time, due to the use of a suitable extrusion forming process, the coarse second phase in the magnesium matrix is broken, avoiding the problem of reducing the degradation rate due to the formation of a corrosion barrier caused by the aggregation of the second phase.
[0017] (2) In order to further balance the degradability and mechanical properties, low concentration of Al was further added to the Mg-Cu alloy to form β-Mg 17 Al 12 phase to improve strength. Al solute atoms can increase the matrix dislocation density, thereby obtaining good plasticity. In addition, the voltaic value of Al is higher than that of Mg, and the β-Mg 17 Al 12 The phase can act as a cathode and increase the corrosion rate.
[0018] (3) In the alloy composition of the present invention, the distribution and amount of the second phase are regulated by regulating the content of Al and Cu to improve the strength, plasticity and degradation performance of the alloy of the present invention. The magnesium alloy can be used for the preparation of fracturing balls in oil drilling, eliminate the plugging phenomenon of oil wells, avoid backflow, and improve mining efficiency and oil resource utilization.
[0019] Through the design of the above alloy components and the processing method, the magnesium alloy of the present invention has good mechanical properties and processing properties, and is easy to dissolve in electrolyte solutions, and is an ideal material for preparing soluble temporary plugging tools. This degradable magnesium alloy has good strength and plasticity and good degradation performance, and has good performance in use. The diameter of the fast-degradable magnesium alloy rod of the present invention can reach 30mm, the tensile strength is 250-280MPa, the elongation reaches 20%, and it has good comprehensive mechanical properties. In a simulated soil environment, the corrosion rate can reach as fast as 0.0211cm / h, which is an ideal material for preparing fracturing balls for oil drilling.
[0020] The present invention also discloses a method for preparing a fast-degradable magnesium alloy for oil drilling, the method comprising material selection, smelting, solution treatment and extrusion treatment. The method carries out alloying to improve the degradation performance and mechanical properties of the magnesium alloy and saves costs. The structure is made more uniform and the formability is better through a suitable homogenization heat treatment process and extrusion deformation, avoiding the problem of deterioration of the mechanical properties and degradation properties caused by the coarsening and aggregation of the precipitated phase in the traditional aging precipitation strengthening, and synergistically improving the comprehensive mechanical properties and degradation properties of the magnesium alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1The room temperature mechanical properties diagram of the fast-degrading magnesium alloy for oil drilling obtained in various embodiments of the present invention; Figure 2 This is a graph showing the degradation rate of the fast-degradable magnesium alloy for oil drilling in a simulated soil environment obtained in various embodiments of the present invention; Figure 3 This is a microstructure diagram of Example 4 of the present invention. DETAILED DESCRIPTION
[0022] The present invention is further described in detail below in conjunction with the accompanying drawings: In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0023] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0024] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0025] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples that do not specify specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples, unless otherwise specified, are conventional commercially available products, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0026] As mentioned in the background technology, in underground stratified and staged fracturing, temporary plugging tools are needed to isolate the layers. After the construction is completed, such temporary plugging tools need to be removed. Therefore, degradable materials are introduced into such tools, so that the temporary plugging workpieces can dissolve themselves underground after completing the fracturing operation, and the backflow or drilling and grinding process can be omitted. This method not only improves the construction efficiency, but also avoids the damage of drill cuttings to the reservoir. In view of this, the development of temporary plugging tools that can degrade by themselves has become the key to solving the above problems. By adding degradable components to the tool materials, these tools can dissolve themselves under specific environmental conditions underground after completing the fracturing operation, and harmless treatment can be achieved without human intervention. This innovative design greatly simplifies the operation process, eliminates cumbersome steps such as backflow or drilling and grinding, not only significantly improves the construction efficiency, but also effectively avoids the potential damage to the reservoir caused by residual drill cuttings, and protects the integrity and long-term production capacity of the oil and gas reservoir.
[0027] Based on the above ideas, the first aspect of the present invention discloses a fast-degrading magnesium alloy for oil drilling, which comprises the following components in terms of mass percentage: Al: 3.0-5.0%; Cu: 2.0-5.0%; The balance is Mg and other unavoidable impurity elements; the alloy includes MgAlCu phase and β-Mg 17 Al 12 The MgAlCu phase is dispersed and fine, and along this phase, due to the large potential difference with the magnesium matrix, it is conducive to the formation of micro-batteries, which can achieve the degradation of the alloy through galvanic corrosion, and at the same time avoid the problem of reducing the degradation rate due to the formation of a corrosion barrier caused by the aggregation of the second phase.
[0028] The second aspect of the present invention discloses a method for preparing a fast-degradable magnesium alloy for oil drilling, comprising the following steps: Step 1, prepare raw materials according to the set mass percentage, the raw materials are industrial pure magnesium ingots, pure aluminum ingots, and pure copper ingots, and weigh them; the purity of the pure magnesium ingots is about 99.85%, and the purity of the pure aluminum ingots and pure copper ingots is greater than 99%.
[0029] Melting: A mixed protective gas of CO2, Ar and SF6 with a volume ratio of 24:75:1 is introduced into the melting furnace, and a low melting point covering agent is added. The covering agent is BaCl2, CaCl2 and MgCl2 mixed in a specific ratio to isolate the air and prevent the magnesium alloy from being oxidized. Then a refining agent is added to dissolve and absorb excess oxides and gases. A magnesium ingot is added, and after the magnesium ingot is completely melted, an aluminum ingot and copper are added in sequence. After the melting furnace is heated to 750°C, a molten metal can be obtained. After removing the surface impurities, the molten metal is cooled to 720°C and kept warm for 15 minutes, and then the molten metal is cast into a mold to obtain a semi-continuous casting.
[0030] After smelting, MgAlCu phase and β-Mg 17 Al 12 phase as the second phase, but the second phase at this time is mostly in an aggregated state.
[0031] Step 2, homogenization treatment: homogenize the casting at 300-320°C for 6-8h, then quench with 70°C warm water and cool to room temperature, and the homogenization treatment is completed.
[0032] Through homogenization solid solution treatment, the second phase gradually diffuses and the entire component system becomes more uniform.
[0033] Step 3, extrusion: the obtained casting is extruded at a temperature of 360-380° C., an extrusion ratio of 9:1, and an extrusion speed of 2 mm / s. After extrusion, it is air-cooled to obtain an extruded rod with a diameter of 30 mm, namely the degradable magnesium alloy for oil drilling.
[0034] Through the extrusion process, the second phase is distributed along the extrusion direction and is more evenly distributed in the final rod.
[0035] The Al- and Cu-containing fast-degradable magnesium alloy for oil drilling of the present invention has good strength, plasticity and degradability, and can be used for preparing fracturing balls in oil drilling.
[0036] The following is further described in conjunction with specific embodiments.
[0037] Example 1 The high-strength and heat-resistant rare earth magnesium alloy containing Al and Cu in this embodiment has a composition ratio of 5.0% Al, 2.0% Cu, and the rest being Mg and other inevitable impurity elements.
[0038] A mixed protective gas of CO2, Ar and SF6 with a volume ratio of 24:75:1 is introduced into the smelting furnace, and a low-melting-point covering agent is added. The covering agent is BaCl2, CaCl2 and MgCl2 mixed in a specific ratio to isolate the air and prevent the magnesium alloy from being oxidized. Then a refining agent is added to dissolve and absorb excess oxides and gases. A magnesium ingot is added, and after the magnesium ingot is completely melted, an aluminum ingot and copper are added in sequence. After the smelting furnace is heated to 750°C, a molten metal can be obtained. After removing the surface impurities, the molten metal is cooled to 720°C and kept warm for 15 minutes, and then the molten metal is cast into a mold to obtain a semi-continuous casting.
[0039] The casting was homogenized at 320°C for 6 h, then quenched in 70°C hot water and cooled to room temperature.
[0040] The obtained casting is extruded at a temperature of 360° C., an extrusion ratio of 9:1, and an extrusion speed of 2 mm / s, and air-cooled after extrusion to obtain an extruded rod with a diameter of 30 mm, namely the fast-degradable magnesium alloy for oil drilling.
[0041] Example 2 The high-strength and heat-resistant rare earth magnesium alloy containing Al and Cu in this embodiment has a composition ratio of 5.0% Al, 3.0% Cu, and the rest being Mg and other inevitable impurity elements.
[0042] A mixed protective gas of CO2, Ar and SF6 with a volume ratio of 24:75:1 is introduced into the smelting furnace, and a low-melting-point covering agent is added. The covering agent is BaCl2, CaCl2 and MgCl2 mixed in a specific ratio to isolate the air and prevent the magnesium alloy from being oxidized. Then a refining agent is added to dissolve and absorb excess oxides and gases. A magnesium ingot is added, and after the magnesium ingot is completely melted, an aluminum ingot and copper are added in sequence. After the smelting furnace is heated to 750°C, a molten metal can be obtained. After removing the surface impurities, the molten metal is cooled to 720°C and kept warm for 15 minutes, and then the molten metal is cast into a mold to obtain a semi-continuous casting.
[0043] The casting was homogenized at 320°C for 8 h, then quenched in 70°C warm water and cooled to room temperature.
[0044] The obtained casting is extruded at a temperature of 380° C., an extrusion ratio of 9:1, and an extrusion speed of 2 mm / s, and air-cooled after extrusion to obtain an extruded rod with a diameter of 30 mm, namely the fast-degradable magnesium alloy for oil drilling.
[0045] Example 3 The high-strength and heat-resistant rare earth magnesium alloy containing Al and Cu in this embodiment has a composition ratio of 5.0% Al, 4.0% Cu, and the rest being Mg and other inevitable impurity elements.
[0046] A mixed protective gas of CO2, Ar and SF6 with a volume ratio of 24:75:1 is introduced into the smelting furnace, and a low-melting-point covering agent is added. The covering agent is BaCl2, CaCl2 and MgCl2 mixed in a specific ratio to isolate the air and prevent the magnesium alloy from being oxidized. Then a refining agent is added to dissolve and absorb excess oxides and gases. A magnesium ingot is added, and after the magnesium ingot is completely melted, an aluminum ingot and copper are added in sequence. After the smelting furnace is heated to 750°C, a molten metal can be obtained. After removing the surface impurities, the molten metal is cooled to 720°C and kept warm for 15 minutes, and then the molten metal is cast into a mold to obtain a semi-continuous casting.
[0047] The casting was homogenized at 300°C for 6 h, then quenched in 70°C hot water and cooled to room temperature.
[0048] The obtained casting is extruded at a temperature of 370°C, an extrusion ratio of 9:1, and an extrusion speed of 2 mm / s, and air-cooled after extrusion to obtain an extruded rod with a diameter of 30 mm, namely the fast-degradable magnesium alloy for oil drilling.
[0049] Example 4 The high-strength and heat-resistant rare earth magnesium alloy containing Al and Cu in this embodiment has a composition ratio of 3.0% Al, 5.0% Cu, and the rest being Mg and other inevitable impurity elements.
[0050] A mixed protective gas of CO2, Ar and SF6 with a volume ratio of 24:75:1 is introduced into the smelting furnace, and a low-melting-point covering agent is added. The covering agent is BaCl2, CaCl2 and MgCl2 mixed in a specific ratio to isolate the air and prevent the magnesium alloy from being oxidized. Then a refining agent is added to dissolve and absorb excess oxides and gases. A magnesium ingot is added, and after the magnesium ingot is completely melted, an aluminum ingot and copper are added in sequence. After the smelting furnace is heated to 750°C, a molten metal can be obtained. After removing the surface impurities, the molten metal is cooled to 720°C and kept warm for 15 minutes, and then the molten metal is cast into a mold to obtain a semi-continuous casting.
[0051] The casting was homogenized at 310°C for 8 h, then quenched in 70°C hot water and cooled to room temperature.
[0052] The obtained casting is extruded at a temperature of 380° C., an extrusion ratio of 9:1, and an extrusion speed of 2 mm / s, and air-cooled after extrusion to obtain an extruded rod with a diameter of 30 mm, namely the fast-degradable magnesium alloy for oil drilling.
[0053] The magnesium alloy bars of Example 1, Example 2, Example 3, and Example 4 were subjected to room temperature mechanical property tests and degradation performance tests in a simulated soil environment. The results are shown in the following table: Table 1 Performance test table of Example 1-Example 4
[0054] From Table 1 and the attached Figure 1 , Figure 2 It can be seen that the tensile strength of the magnesium alloy chamber of Example 1, Example 2, Example 3, and Example 4 is 254.03-283.85MPa, and the elongation is 19.05-24.49%, which has good comprehensive mechanical properties and can meet the mechanical property requirements of fracturing balls for oil drilling. The degradation performance of Example 4 can reach 0.0211cm / h, which has good degradation performance. This degradable magnesium alloy rod can be used for industrial production.
[0055] In the present invention, Al and Cu are alloying elements with low cost and good economic value. These two elements can form a solid solution in Mg to improve the strength of the magnesium alloy, and can also form a fine dispersed precipitate phase to hinder dislocation movement and thus improve the mechanical properties of the magnesium alloy. Figure 3 It can be seen that the second phase in the alloy of Example 4 is distributed along the extrusion direction to form an obvious extrusion streamline, and relatively complete dynamic recrystallization occurs. According to the particle stimulated nucleation (PSN) mechanism of recrystallization, these micron-sized precipitated phases can hinder the further growth of recrystallized grains, which is beneficial to improving the comprehensive mechanical properties of magnesium alloys. In addition, these second phases are mainly β-Mg 17 Al 12 The volt potential of these second phases is higher than that of the Mg matrix, which acts as a cathode to accelerate galvanic corrosion. At the same time, these second phases are dispersed and evenly distributed in the magnesium matrix, avoiding the problem of reducing the degradation rate due to the formation of corrosion barriers caused by the aggregation of the second phases.
[0056] Example 5 The high-strength and heat-resistant rare earth magnesium alloy containing Al and Cu in this embodiment has a composition ratio of 4.0% Al, 3.0% Cu, and the rest being Mg and other inevitable impurity elements in weight percentage.
[0057] A mixed protective gas of CO2, Ar and SF6 with a volume ratio of 24:75:1 is introduced into the smelting furnace, and a low-melting-point covering agent is added. The covering agent is BaCl2, CaCl2 and MgCl2 mixed in a specific ratio to isolate the air and prevent the magnesium alloy from being oxidized. Then a refining agent is added to dissolve and absorb excess oxides and gases. A magnesium ingot is added, and after the magnesium ingot is completely melted, an aluminum ingot and copper are added in sequence. After the smelting furnace is heated to 750°C, a molten metal can be obtained. After removing the surface impurities, the molten metal is cooled to 720°C and kept warm for 15 minutes, and then the molten metal is cast into a mold to obtain a semi-continuous casting.
[0058] The casting was homogenized at 310°C for 7 h, then quenched with 70°C warm water and cooled to room temperature.
[0059] The obtained casting is extruded at a temperature of 370°C, an extrusion ratio of 9:1, and an extrusion speed of 2 mm / s, and air-cooled after extrusion to obtain an extruded rod with a diameter of 30 mm, namely the fast-degradable magnesium alloy for oil drilling.
[0060] Example 6 The high-strength and heat-resistant rare earth magnesium alloy containing Al and Cu in this embodiment has a composition ratio of 4.0% Al and 5.0% Cu by weight, with the remainder being Mg and other inevitable impurity elements.
[0061] A mixed protective gas of CO2, Ar and SF6 with a volume ratio of 24:75:1 is introduced into the smelting furnace, and a low-melting-point covering agent is added. The covering agent is BaCl2, CaCl2 and MgCl2 mixed in a specific ratio to isolate the air and prevent the magnesium alloy from being oxidized. Then a refining agent is added to dissolve and absorb excess oxides and gases. A magnesium ingot is added, and after the magnesium ingot is completely melted, an aluminum ingot and copper are added in sequence. After the smelting furnace is heated to 750°C, a molten metal can be obtained. After removing the surface impurities, the molten metal is cooled to 720°C and kept warm for 15 minutes, and then the molten metal is cast into a mold to obtain a semi-continuous casting.
[0062] The casting was homogenized at 310°C for 7 h, then quenched with 70°C warm water and cooled to room temperature.
[0063] The obtained casting is extruded at a temperature of 360° C., an extrusion ratio of 9:1, and an extrusion speed of 2 mm / s, and air-cooled after extrusion to obtain an extruded rod with a diameter of 30 mm, namely the fast-degradable magnesium alloy for oil drilling.
[0064] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A fast-degradable magnesium alloy for oil drilling, characterized in that: In terms of mass percentage, it includes: Al:3.0-5.0%; Cu: 2.0-5.0%; The balance is Mg and other unavoidable impurity elements; The magnesium alloy contains MgAlCu phase and β-Mg 17 Al 12 Mutually.
2. The fast-degrading magnesium alloy for oil drilling according to claim 1, characterized in that: The magnesium alloy has a tensile strength of 250-280 MPa and a maximum elongation of 20%.
3. A method for preparing a fast-degradable magnesium alloy for oil drilling according to claim 1, characterized in that: The following steps are involved: Step 1, weighing the raw materials according to the set mass, placing the raw materials in a heating furnace, and pouring after melting to obtain a semi-continuous casting; Step 2, homogenizing the semi-continuous casting and obtaining a process part after quenching; Step 3, obtaining a magnesium alloy by extruding the process part.
4. The method for preparing a fast-degradable magnesium alloy for oil drilling according to claim 3, characterized in that: In step 1, the raw materials are pure magnesium ingots, pure aluminum ingots and pure copper ingots.
5. The method for preparing a fast-degradable magnesium alloy for oil drilling according to claim 3, characterized in that: In step 1, the melting temperature is 750°C and the pouring temperature is 720°C.
6. The method for preparing a fast-degradable magnesium alloy for oil drilling according to claim 3, characterized in that: In step 1, during the smelting process, a mixed protective gas is added, and the protective gas consists of CO2, Ar and SF6.
7. The method for preparing a fast-degradable magnesium alloy for oil drilling according to claim 3, characterized in that: In step 2, the homogenization temperature is 300-320° C. and the homogenization temperature is 6-8 hours.
8. The method for preparing a fast-degradable magnesium alloy for oil drilling according to claim 3, characterized in that: In step 2, the quenching temperature is 70°C.
9. The method for preparing a fast-degradable magnesium alloy for oil drilling according to claim 3, characterized in that: In step 3, the extrusion temperature is 360-380°C.
10. The method for preparing a fast-degradable magnesium alloy for oil drilling according to claim 3, characterized in that: In step 3, the extrusion ratio is 9:1 and the extrusion speed is 2 mm / s.